Data from a prospective study of the features of systemic lupus erythematosus in patients of Kyrgyzstan (Eurasian RENAISSANCE Register) - G. M. Koilubaeva; E. A. Aseeva; S. K. Solovyev; E. R. Karimova; N. Yu. Nikishina; F. S. Dzhuzenova; A. M. Lila; E. L. Nasonov; E. Zh. Dzhichambaev (Современная ревматология)
Objective: to study and analyze the clinical and laboratory manifestations, course, and outcome of systemic lupus erythematosus (SLE) in patients living in Kyrgyzstan.Patients and methods. The prospective study included 150 young patients aged 34 [26, 44] years in a Kyrgyz cohort (KC) with SLE, the disease of which was 3.0 [0.7; 10] years. All clinical, laboratory, and instrumental data of patients, health-related quality of life (HRQOL) indicators, and treatment regimens were recorded in the international research base, such as British Lupus Integrated Prospective System (BLIPS). SLE activity was assessed using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K). At the end of the observation, the investigators assessed the following indicators: the number of exacerbations of SLE by the SELENA Flare Index (SFI); the onset of complete or drug-induced remission; the number of deaths; and the development of irreversible organ damages (IOD) according to the damage index (DI).Results and discussion. When seeing the physician for the first time, the KC included more patients with high (n=61 (40.66%)) and very high (n=40 (26.67%)) disease activity. Most (n=60 (40%)) patients were observed to have a subacute type of the course of the disease. At the first visit, the most common manifestations of SLE were damages to the skin (n=99 (72.67%)), serous membranes (n=91 (60.67%)), and lupus nephritis (n=79 (52.67%)). IODs were identified in 15.33% of the patients and were absent in 84.67%. IODs were more often due to the administration of glucocorticoids (GCs) in 43.48% of cases. However, GC therapy was not a predictor of organ damages (relative risk, 0.91; p>0.05). In the KC, the significant predictors of adverse outcomes were old-age onset SLE and its high activity, acute course, and frequent exacerbations.Conclusion. The KC patients had high and very high clinical and laboratory activities (40.6 and 26.6%, respectively), mainly those of acute and subacute SLE (32 and 40%, respectively), obvious immunological disorders. There was a preponderance of damages to the skin (73%), serous membranes (61%), and kidney (53%) among the clinical manifestations of SLE. IODs were found in 15.33% of patients at their study inclusion. These were more frequently represented by GC-induced changes. However, the ongoing GC therapy in the KC patients was not a predictor of organ damages. The significant predictors of an adverse outcome in our patients were old-age onset SLE and its high activity, acute course, and frequent exacerbations.